2014
DOI: 10.4137/cin.s14035
|View full text |Cite
|
Sign up to set email alerts
|

Automated Recommendation for Cervical Cancer Screening and Surveillance

Abstract: Because of the complexity of cervical cancer prevention guidelines, clinicians often fail to follow best-practice recommendations. Moreover, existing clinical decision support (CDS) systems generally recommend a cervical cytology every three years for all female patients, which is inappropriate for patients with abnormal findings that require surveillance at shorter intervals. To address this problem, we developed a decision tree-based CDS system that integrates national guidelines to provide comprehensive gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…al. [44] used a decision tree to create an automated clinical decision support (CDS) system, in which Natural Language Processing identified the parameters from cervical pathology and clinical notes. Again, Nuranna et.…”
Section: Plos Onementioning
confidence: 99%
“…al. [44] used a decision tree to create an automated clinical decision support (CDS) system, in which Natural Language Processing identified the parameters from cervical pathology and clinical notes. Again, Nuranna et.…”
Section: Plos Onementioning
confidence: 99%
“…In earlier works, 13 14 15 16 Wagholikar et al described the implementation of a CDSS for Cervical Cancer Screening and Surveillance (CCSS). The system utilized natural language processing (NLP) to extract variables about cervical cancer screening from cytology reports generated after Pap smear screening and pathology reports from colposcopy biopsies, which are predominantly available in text format.…”
Section: Background and Significancementioning
confidence: 99%
“…It cannot confuse one patient for another, it cannot combine medical records of more than one patient to make a decision, it eliminates medical errors in the absence of human errors, it will not be exhausted or overwhelm to produce a wrong decision, it cannot base its decisions on feelings or instincts, or on the appearance of the patient, it has so many positive outlook and it is facilitating conditions (incorporating workflow, training and integration), ease of use and trust in the knowledge base 89 . In another study testing the impact of CDSS, providers without CDSS assistance needed an average of 1 minute 39 seconds to decide on recommendations for management of abnormal findings 90 . Another study showed that CDSS has the potential to decrease malpractice payments because of its known benefits for quality and safety 91 .…”
Section: Advantages Of Clinical Decision Support Systemsmentioning
confidence: 99%